2019
DOI: 10.1111/1747-0080.12520
|View full text |Cite
|
Sign up to set email alerts
|

Waist to height ratio is the anthropometric index that most appropriately mirrors the lifestyle and psychological risk factors of obesity

Abstract: Aim To determine to what extent the lifestyle and psychological factors influenced the occurrence of obesity in the population of the Mediterranean island of Vis (Croatia); also to relate the examined risk factors to several obesity indicators in order to select the most sensitive one. Methods Cross‐sectional population study included 960 participants of both sexes (18–93 years) in whom the obesity was estimated using anthropometric indicators. The factor analysis of 55‐item Food Frequency Questionnaire (FFQ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…22 The association between abnormal eating behaviors and waist-to-height ratio reported in our study is in agreement with the findings of a study conducted in Croatia among adults aged between 18 and 93 years, which reported that waist-to-height ratio is the most important anthropometric measure in terms of predicting lifestyle and psychological risks for obesity. 23 Lifestyle factors such as the availability of convenience and fast food, study time patterns, and staying alone and away from home might contribute to abnormal eating attitudes. Lack of physical activity can also contribute to an increase in body weight and a resulting change in eating habits.…”
Section: Discussionmentioning
confidence: 99%
“…22 The association between abnormal eating behaviors and waist-to-height ratio reported in our study is in agreement with the findings of a study conducted in Croatia among adults aged between 18 and 93 years, which reported that waist-to-height ratio is the most important anthropometric measure in terms of predicting lifestyle and psychological risks for obesity. 23 Lifestyle factors such as the availability of convenience and fast food, study time patterns, and staying alone and away from home might contribute to abnormal eating attitudes. Lack of physical activity can also contribute to an increase in body weight and a resulting change in eating habits.…”
Section: Discussionmentioning
confidence: 99%
“…However, BMI has an obvious limitation, it may not be able to distinguish excess adipose tissue [ 40 , 41 ], while WC is an excellent indicator of visceral obesity. In recent years, more and more studies have found that WHtR, which combines height and WC, is a better alternative indicator of obesity, and it is also a better determinant of NAFLD risk than BMI and WC [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, common criticisms include an inability to distinguish between lean body mass and fat mass and the difference across ethnic groups and by age, highlighting the need for more sensitive methods. 37 In this issue, Tomas et al 38 reported a cross-sectional comparison of obesity indices, including BMI, waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), sum of skinfold thicknesses (biceps, triceps, subscapular, suprailiac and abdominal) and body fat mass percentage (FAT) estimated using bioelectrical impedance, to evaluate the most sensitive instrument for detecting the influences of various risk factors on obesity. They report WHtR as a more sensitive indicator of obesity than BMI and more strongly related to body composition and risk factors related to overweight/ obesity, such as diet, lifestyle and psychological factors.…”
Section: Malnutritionmentioning
confidence: 99%
“…They report WHtR as a more sensitive indicator of obesity than BMI and more strongly related to body composition and risk factors related to overweight/ obesity, such as diet, lifestyle and psychological factors. 38 Reducing disability secondary to chronic disease by prolonging mobility and self-care is key to lowering costs of long-term care to families and society and requires early detection of chronic disease risk factors. 35 Sarcopenia, a skeletal muscle disorder commonly associated with aging, is associated with adverse outcomes including falls, functional decline, frailty, mortality and prolonged hospital admission.…”
Section: Malnutritionmentioning
confidence: 99%